Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Certainly! Let's solve this step by step.
We are given the sum of the first [tex]\( n \)[/tex] terms of an arithmetic series as [tex]\( 209 \)[/tex]. The first term ([tex]\( a \)[/tex]) is [tex]\( 4 \)[/tex], and the common difference ([tex]\( d \)[/tex]) is [tex]\( 3 \)[/tex]. We need to find the value of [tex]\( n \)[/tex].
First, let's recall the formula for the sum of the first [tex]\( n \)[/tex] terms of an arithmetic series:
[tex]\[ S_n = \frac{n}{2} \left(2a + (n - 1)d\right) \][/tex]
Plugging in the values we know:
[tex]\[ 209 = \frac{n}{2} \left(2 \cdot 4 + (n - 1) \cdot 3\right) \][/tex]
Simplify inside the parentheses:
[tex]\[ 209 = \frac{n}{2} \left(8 + 3(n - 1)\right) \][/tex]
[tex]\[ 209 = \frac{n}{2} \left(8 + 3n - 3\right) \][/tex]
[tex]\[ 209 = \frac{n}{2} \left(3n + 5\right) \][/tex]
Next, eliminate the fraction by multiplying both sides by [tex]\( 2 \)[/tex]:
[tex]\[ 418 = n(3n + 5) \][/tex]
Rearrange the equation into standard quadratic form:
[tex]\[ 3n^2 + 5n - 418 = 0 \][/tex]
Now, solve this quadratic equation using the quadratic formula [tex]\( n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 3 \)[/tex], [tex]\( b = 5 \)[/tex], and [tex]\( c = -418 \)[/tex].
First, calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = 5^2 - 4 \cdot 3 \cdot (-418) \][/tex]
[tex]\[ \Delta = 25 + 5024 \][/tex]
[tex]\[ \Delta = 5049 \][/tex]
Now, apply the quadratic formula:
[tex]\[ n = \frac{-5 \pm \sqrt{5049}}{2 \cdot 3} \][/tex]
Calculate the roots:
[tex]\[ n_1 = \frac{-5 + \sqrt{5049}}{6} \][/tex]
[tex]\[ n_2 = \frac{-5 - \sqrt{5049}}{6} \][/tex]
Evaluating these roots:
[tex]\[ n_1 \approx \frac{-5 + 71.05}{6} \approx \frac{66.05}{6} \approx 11.01 \][/tex]
[tex]\[ n_2 \approx \frac{-5 - 71.05}{6} \approx \frac{-76.05}{6} \approx -12.68 \][/tex]
Since [tex]\( n \)[/tex] must be a positive integer, we discard the negative root:
[tex]\[ n = 11 \][/tex]
Therefore, the number of terms [tex]\( n \)[/tex] is:
[tex]\[ \boxed{11} \][/tex]
We are given the sum of the first [tex]\( n \)[/tex] terms of an arithmetic series as [tex]\( 209 \)[/tex]. The first term ([tex]\( a \)[/tex]) is [tex]\( 4 \)[/tex], and the common difference ([tex]\( d \)[/tex]) is [tex]\( 3 \)[/tex]. We need to find the value of [tex]\( n \)[/tex].
First, let's recall the formula for the sum of the first [tex]\( n \)[/tex] terms of an arithmetic series:
[tex]\[ S_n = \frac{n}{2} \left(2a + (n - 1)d\right) \][/tex]
Plugging in the values we know:
[tex]\[ 209 = \frac{n}{2} \left(2 \cdot 4 + (n - 1) \cdot 3\right) \][/tex]
Simplify inside the parentheses:
[tex]\[ 209 = \frac{n}{2} \left(8 + 3(n - 1)\right) \][/tex]
[tex]\[ 209 = \frac{n}{2} \left(8 + 3n - 3\right) \][/tex]
[tex]\[ 209 = \frac{n}{2} \left(3n + 5\right) \][/tex]
Next, eliminate the fraction by multiplying both sides by [tex]\( 2 \)[/tex]:
[tex]\[ 418 = n(3n + 5) \][/tex]
Rearrange the equation into standard quadratic form:
[tex]\[ 3n^2 + 5n - 418 = 0 \][/tex]
Now, solve this quadratic equation using the quadratic formula [tex]\( n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 3 \)[/tex], [tex]\( b = 5 \)[/tex], and [tex]\( c = -418 \)[/tex].
First, calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = 5^2 - 4 \cdot 3 \cdot (-418) \][/tex]
[tex]\[ \Delta = 25 + 5024 \][/tex]
[tex]\[ \Delta = 5049 \][/tex]
Now, apply the quadratic formula:
[tex]\[ n = \frac{-5 \pm \sqrt{5049}}{2 \cdot 3} \][/tex]
Calculate the roots:
[tex]\[ n_1 = \frac{-5 + \sqrt{5049}}{6} \][/tex]
[tex]\[ n_2 = \frac{-5 - \sqrt{5049}}{6} \][/tex]
Evaluating these roots:
[tex]\[ n_1 \approx \frac{-5 + 71.05}{6} \approx \frac{66.05}{6} \approx 11.01 \][/tex]
[tex]\[ n_2 \approx \frac{-5 - 71.05}{6} \approx \frac{-76.05}{6} \approx -12.68 \][/tex]
Since [tex]\( n \)[/tex] must be a positive integer, we discard the negative root:
[tex]\[ n = 11 \][/tex]
Therefore, the number of terms [tex]\( n \)[/tex] is:
[tex]\[ \boxed{11} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.